Energy Poverty and Health Care Expenditures: Evidence from the China Family Panel Studies - Peng Nie; Qiaoge Li (Institute of Labor Economics (IZA), 2022)
Using the 2012-2018 waves of the China Family Panel Studies (CFPS), we investigate the impact of energy poverty (EP) on health care expenditures among Chinese adults aged 18+. Employing a methodology combining a random effects two-part model and instrumental variable estimations, we show that EP leads to higher levels of total (305 yuan), out-of-pocket (199 yuan), inpatient (230 yuan) and other (113 yuan) health care expenditures, with more pronounced impacts among females and those living in urban areas and Central and Western China. These results are robust not only to alternative EP and health care expenditure measures but also to a series of estimation approaches that control for endogeneity. An additional structural equation modeling analysis of the underlying pathways further reveals that this EP-health care expenditure relationship is mediated by individual self-reported health as well as expenditures on food and other daily necessities.
Keywords: I10; I11; I32; Q40; R21; 330; energy poverty; health care expenditures; China